Magnetic Enrichment of SARS-CoV-2 Antigen-Binding B Cells for Analysis of Transcriptome and Antibody Repertoire - Maureen Banach; Isaac T. W. Harley; Mary K. McCarthy; Cody Rester; Adonis Stassinopoulos; Ross M. Kedl; Thomas E. Morrison; John C. Cambier (Magnetochemistry, 2022)
The ongoing COVID-19 pandemic has had devastating health impacts across the globe. The development of effective diagnostics and therapeutics will depend on the understanding of immune responses to natural infection and vaccination to the causative agent of COVID-19, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). While both B-cell immunity and T-cell immunity are generated in SARS-CoV-2-infected and vaccinated individuals, B-cell-secreted antibodies are known to neutralize SARS-CoV-2 virus and protect from the disease. Although interest in characterizing SARS-CoV-2-reactive B cells is great, the low frequency of antigen-binding B cells in human blood limits in-depth cellular profiling. To overcome this obstacle, we developed a magnetic bead-based approach to enrich SARS-CoV-2-reactive B cells prior to transcriptional and antibody repertoire analysis by single-cell RNA sequencing (scRNA-seq). Here, we describe isolation of SARS-CoV-2 antigen-binding B cells from two seropositive donors and comparison to nonspecific B cells from a seronegative donor. We demonstrate that SARS-CoV-2 antigen-binding B cells can be distinguished on the basis of transcriptional profile and antibody repertoire. Furthermore, SARS-CoV-2 antigen-binding B cells exhibit a gene expression pattern indicative of antigen experience and memory status. Combining scRNA-seq methods with magnetic enrichment enables the rapid characterization of SARS-CoV-2 antigen-binding B cells.